Penerapan Internet Of Things Untuk Sistem Pengendalian Lampu Taman Berbasis NODEMCU ESP8266 - Muhamad Kiflan Affandi; budi Darmawan; Paniran (Depertment of Electrical Engineering University of Mataram, 2023)
This study involves the use of NodeMCU ESP8266, an affordable and user-friendly Wi-Fi-based microcontroller module. NodeMCU ESP8266 is used as the main brain in the IoT system, responsible for collecting data from sensors and sending it via Wi-Fi connection to the server. As evening approaches, NodeMCU ESP8266 will send a signal to the relay to turn on the lights. Conversely, as morning approaches, NodeMCU ESP8266 will send a signal to the relay to turn off the lights. Additionally, users can control the garden lights through Telegram, which is connected to the IoT system. Telegram allows users to manually control the garden light illumination according to their needs. Users can also manually set schedules to turn the lights on or off. In this study, the implementation of an IoT-based garden light control system using NodeMCU ESP8266 has been successfully carried out. This system demonstrates reliability and flexibility in automatically and manually controlling the garden lights. The implementation of IoT in garden light control can provide benefits such as energy efficiency, convenience, and ease of use.